On the Carbon Kinetics in Martensite, relevance to Nanosegregation at Dislocations and Grain Boundaries - Nechaev, Yury S. (Diffusion Fundamentals, 2017)
This short communication is devoted to the room temperature processes of diffusion and redistribution of dissolved carbon atoms in martensite to the nanosegregation regions at dislocations and grain boundaries. It is related to the DF7 contribution of M. Lavrskyi et al. on the carbon kinetics in martensite [1] and to the DF7 contribution of Yu. Nechaev on the compound-like nanosegregation at dislocations and grain boundaries in metallic materials.